GETTING TO GRIPS WITH DIGITAL TRANSFORMATION. Issue 1 (March 2016) - Birkinshaw, Julian; Robbins, Peter; Ryan, Johnny
Abstract : Even mature companies can use startup tactics.Peter Robbins, Julian Birkinshaw andJohnny Ryan examine The Irish Times